Membangun Interaksi Edukatif yang Bernilai Normatif Melalui Pengajaran Berbasis Aktifitas - Hawa Liberna (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2012)
To solve the problem of students' interest in mathematics, we need a model of interactive learning and not boring. It is important to establish educational interactions, and one of them to do with the activity-based teaching. Learning is an activity-oriented action research and reflective study is conducted in the classroom, as well as aiming to improve the quality of learning. This process is applied to the